Super psychology : a totally non-scary guide to psychology and what it means - Jarrett, Christian; Ginsburg, Joannah (London New Burlington Books, 2017)
Packed with illuminating images and everyday-life examples, this book explores the human mind in one easy step at a time. Why do we fall in love? What is the secret of a good night's sleep? What happens to forgotten memories? These questions, and many others, will be answered in this book.
Includes index.
Keywords: Psychology -- Popular works; Psychology; Popular works